2006
DOI: 10.1002/jclp.20310
|View full text |Cite
|
Sign up to set email alerts
|

Stages of change as a correlate of mental health symptoms in abused, low-income African American women

Abstract: The current study aims to further our understanding of the applicability of the transtheoretical model (TM) to intimate partner violence (IPV), with particular focus on mental health symptoms (depression, posttraumatic stress disorder symptomatology, suicidal ideation) in a sample of lowincome African American women seeking medical services at an inner city emergency department. Results revealed that of the 121 abused African American women, the majority (95%) were in the precontempla-tion and contemplation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 57 publications
5
25
0
2
Order By: Relevance
“…They are consistent with prior studies demonstrating the significance of the change process for abused women (Chang et al, 2006; Edwards et al, 2006). Moreover, research demonstrates that stage in the change process predicts outcomes in perpetrators of IPV (Alexander & Morris, 2008; Eckhardt, Babcock, & Homack, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…They are consistent with prior studies demonstrating the significance of the change process for abused women (Chang et al, 2006; Edwards et al, 2006). Moreover, research demonstrates that stage in the change process predicts outcomes in perpetrators of IPV (Alexander & Morris, 2008; Eckhardt, Babcock, & Homack, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…These findings support and build upon prior studies that have suggested a link between PTSD symptoms and women being trapped in dangerous abusive relationships (Edwards et al, 2006; Perez Johnson, 2008). PTSD symptoms may develop due to “chronic traumatization” or “repeated exposure to traumatic stressors (e.g., serious physical assault, psychological abuse in the form of threats) within the same overall context over time (Kaysen, Resick, Wise, 2003; p.247).…”
Section: Discussionsupporting
confidence: 88%
“…The TTM was originally developed as a general model for understanding behavioural change (Prochaska and Velicer 1997) but has recently been applied to family violence research (Catallo, et al 2012;Edwards et al 2006). It offers valuable insight into understanding the behaviour of victims and perpetrators of family violence.…”
Section: Theoretical Frameworkmentioning
confidence: 99%